Dual vector control strategy for a three-stage hybrid cascaded multilevel inverter - Kadir, M.N.A.; Mekhilef, Saad; Ping, H.W. (2010)
This paper presents a voltage control algorithm for a hybrid multilevel inverter based on a staged-perception of the inverter voltage vector diagram. The algorithm is applied to control a three-stage eighteen-level hybrid inverter, which has been designed with a maximum number of symmetrical levels. The inverter has a two-level main stage built using a conventional six-switch inverter and medium- and low- voltage three-level stages constructed using cascaded H-bridge cells. The distinctive feature of the proposed algorithm is its ability to avoid the undesirable high switching frequency for high- and medium- voltage stages despite the fact that the inverter's dc sources voltages are selected to maximize the number of levels by state redundancy elimination. The high- and medium- voltage stages switching algorithms have been developed to assure fundamental switching frequency operation of the high voltage stage and not more than few times this frequency for the medium voltage stage. The low voltage stage is controlled using a SVPWM to achieve the reference voltage vector exactly and to set the order of the dominant harmonics. The inverter has been constructed and the control algorithm has been implemented. Test results show that the proposed algorithm achieves the desired features and all of the major hypotheses have been verified.